Tricks - Hopkins, Ellen (New York : Margaret K. McElderry Books, 2009)
Five troubled teenagers fall into prostitution as they search for freedom, safety, community, family, and love.
Keywords: Novels in verse -- Juvenile fiction; Family problems -- Juvenile fiction; Emotional problems -- Juvenile fiction; Prostitution -- Juvenile fiction